The Sustainable Infrastructure through the Construction Supply Chain Carbon Footprint Approach. (2017) - Hermawan,; Marzuki, Puti F.; Abduh, Muhamad; Driejana, R.
Abstract: The sustainable development concept is an important issue in construction industry, which becomes important mainly because of its role in infrastructure provision. Infrastructure availability will affect economic growth and increase a country's competitiveness. Indonesia as a developing country still needs to build a lot of physical infrastructure. The concept of sustainable infrastructure development is in line with the Indonesian government's development plans for the period of 2014-2015 called Nawa Cita. Carbon footprint modelling is one of the methods that contributes to the realization of sustainable infrastructure development. This paper describes the approach of sustainable infrastructure development through carbon footprinting in the construction supply chain. In the construction industry, carbon footprinting gives information in total emission of carbon dioxide (CO2 ) in every stage of a construction project's supply chain activities. In creating a carbon footprint model, life cycle analysis (LCA) is used as a supporting instrument to estimate the carbon dioxide (CO2 ) emissions in each stage of the supply chain activities. It is shown that the implementation of sustainable infrastructure development needs a synergy from all parties involved in the construction supply chain.